Analisis Nilai Pelanggan dan Pengalaman Pelanggan terhadap Kepercayaan Pelanggan Wisata Kuliner Selamat Toserba Sukabumi - Nurinda Rahmawati; Asep M. Ramdan; Acep Samsudin (IPM2KPE, 2019)
The purpose of this study was to find out customer value and customer experience towards customer trust in the Happy Toserba Sukabumi Culinary Tourism. The research method used by the authors in this study used a system of random sampling where the authors distributed questionnaires to 100 customers. The analysis technique used by the writer is to use multiple linear regression analysis techniques, multiple correlation coefficient and determination coefficient and for hypothesis testing the author uses partial statistical tests (t test) and simultaneous tests (f test). The results of the study, using the determination coefficient test shows the value (Adjuster R2) of 0.437 which means the influence of customer experience on customer trust is 43.7% and 56.3% is influenced by other factors not examined. In addition, testing multiple correlation coefficients shows an R value of 0.669 which means there is a strong relationship between customer experience and customer trust. Conclusions, customer value and customer experience have a positive and significant effect together on customer trust Keywords: Customer Value, Customer Experience, Customer Trust